The application of bioethics as legal basis in judicial sentences concerning right to health in Brazil - Mariot, Evandro Antonio Sbalcheiro; Barbas, Stela; Nunes, Rui (Acta Bioethica, 2024)
The right to health is linked to life and human dignity. Among the instruments to make it effective, the phenomenon of health litigation has become prominent. In Brazil, courts are increasingly faced with the task of rendering verdicts concerning matters related to health. Nowadays, judges have to deal with issues about health policies, technology incorporations, drug supplies, human autonomy, genetics, and biotechnologies, among others. Lawsuit sentences are now to be built upon the resolution of ethical, legal and philosophical questions. Bioethics presents itself as an instrument and method to help solve legal cases involving the right to health. This paper intends to show that bioethics can be applied in verdicts of lawsuits regarding to right to health in Brazil. It highlights that bioethics can be considered a source of law due to its normative dimension, as well as a hermeneutic method. This essay also aims to show the role for bioethics to help interpret the law and solve hard cases within health law and the right to health. Lastly, it aims to justify the presence of bioethics as legal reasoning to be used by judges in the foundation of their verdicts in lawsuits involving the right to health.